2000
DOI: 10.1016/s0035-9203(00)90112-3
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the spread of human visceral leishmaniasis in central Tunisia

Abstract: The epidemiology, clinical patterns, and spatial spread of Mediterranean visceral leishmaniasis were retrospectively studied in central Tunisia. The clinical profile of the disease was typical of the Mediterranean infantile form. Malnutrition and associated infectious diseases were observed in 62.5% and 55% of cases, respectively. The case-fatality rate was 6.2% and resistance to meglumine antimonate was observed in 1.6% of patients. The annual incidence of cases increased from approximately 10 cases per year … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
44
0
5

Year Published

2005
2005
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(49 citation statements)
references
References 7 publications
0
44
0
5
Order By: Relevance
“…However, in this study, we found that Kairouan, which is an arid region, supposed to be of very low endemicity 30 years ago (Dedet et al, 1973), had a prevalence as high as 20.9 %. This result may be due to: i) the increase of the disease in this region which has not been studied since 1973 in correlation with the important number of cases of Human visceral leishmaniais emerged recently (Ben Salah et al, 2000), and suggesting for a spread of the disease in the centre of Tunisia (Ayadi et al, 1991;Besbes et al, 1994;Ben Salah et al, 2000); ii) the prevalence was underestimated since all previous studies were conducted by serological methods, which, as we reported in this study, can not detect all infected dogs.…”
Section: Prevalence and State Of Canl In Kairouan (Central Tunisia)mentioning
confidence: 99%
See 1 more Smart Citation
“…However, in this study, we found that Kairouan, which is an arid region, supposed to be of very low endemicity 30 years ago (Dedet et al, 1973), had a prevalence as high as 20.9 %. This result may be due to: i) the increase of the disease in this region which has not been studied since 1973 in correlation with the important number of cases of Human visceral leishmaniais emerged recently (Ben Salah et al, 2000), and suggesting for a spread of the disease in the centre of Tunisia (Ayadi et al, 1991;Besbes et al, 1994;Ben Salah et al, 2000); ii) the prevalence was underestimated since all previous studies were conducted by serological methods, which, as we reported in this study, can not detect all infected dogs.…”
Section: Prevalence and State Of Canl In Kairouan (Central Tunisia)mentioning
confidence: 99%
“…Human visceral leishmaniasis is known to be detected occasionally in the central Tunisia (Ayadi et al, 1991;Besbes et al, 1994). However, an important number of cases emerged recently in this region (Ben Salah et al, 2000). Tested dogs were examined for clinical signs of the disease, including dermatological lesions, ocular changes, lost of weight, apathy, lymph node and spleen enlargement.…”
mentioning
confidence: 99%
“…3 Human infection by Leishmania infantum often runs a subclinical and self-healing course (1), but is also featured by the fatal syndrome of infantile visceral leishmaniasis (VL) (2).…”
Section: Mechanisms Of the Natural Reactivity Of Lymphocytes From Nonmentioning
confidence: 99%
“…Indeed, many studies were carried on the prevalence of cutaneous and visceral leishmaniasis in Tunisia but the characterization of the parasite was hardly ever made (Ben Salah et al, 2000;Kharfi et al, 2004). Previously, 65 was the largest number of identified VL strains.…”
Section: Discussionmentioning
confidence: 99%